MTBE Remediation Handbook 2003
DOI: 10.1007/978-1-4615-0021-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of MTBE—A Review of the State of the Technology

Abstract: California State Water Resources Control BoardPhytoremediation is the use of plants to clean up environmental problems. While some have termed this technology a niche strategy, there are almost as many uses of phytoremediation as there are sites and problems. No plant will be able to survive in pure phase contamination, but in areas with low to moderate levels of contaminants, plants can perform a variety of functions. They can enhance the metabolism of microorganisms in the soil and thus the degradation of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Therefore, the results of the present study suggest microbial turnover of MTBE within the wetland plants. Actual potential of MTBE for phytodegradation is outlined by Newman and Arnold, including studies with alfalfa and hybrid poplars.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the results of the present study suggest microbial turnover of MTBE within the wetland plants. Actual potential of MTBE for phytodegradation is outlined by Newman and Arnold, including studies with alfalfa and hybrid poplars.…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory studies, Ma et al [9] found that not only was MTBE released from the leaves, as reported in several previous studies, but it also diffused from the trunk of the plants. A more recent study of five mature Monterey pines exposed to MTBE in the aquifer reported much higher levels of tert-butyl alcohol (TBA) than MTBE through the transpiration stream, indicating that metabolism was taking place either in the rhizosphere or within the plant system [10 ]. This study also showed a significant decrease in MTBE levels in the aquifer as it passed under the trees, indicating that phytoremediation may be a viable option for MTBE, even if the fate of the compound in the plant is not yet fully understood.…”
Section: Phytoremediation Of Solventsmentioning
confidence: 97%
“…The fate of MTBE that is not transpired in plant cells is not entirely known (Newman and Arnold 2003). Typically, the transformation of ethers like MTBE would follow an oxidation pathway of Phase I detoxification.…”
Section: Plant Transformation Reactionsmentioning
confidence: 99%